Integrated Ergonomic Risk Assessment Using NBM, REBA and NIOSH Multitask Analysis for Sustainable Logistics: A Case Study of PT SHJ - Theresia Amelia Pawitra; Siagian Jevendra Vablo Gloria; Yudi Sukmono (Malikussaleh University, Aceh, Indonesia, 2026)
Musculoskeletal disorders (MSDs) remain one of the leading occupational health problems in manual material handling activities, adversely affecting workers' well-being, operational efficiency, and long-term organizational sustainability. This study aimed to comprehensively assess ergonomic risks in the Logistics Department of PT Surya Hutani Jaya, an industrial plantation forestry company in Indonesia, by integrating workers' subjective complaints with objective ergonomic and biomechanical assessments. A descriptive quantitative case study was conducted using a total sampling approach involving five logistics workers performing three critical activities: incoming goods handling, chemical mixing, and fuel inspection. Data were collected using the Nordic Body Map (NBM) questionnaire to identify musculoskeletal complaints, the Rapid Entire Body Assessment (REBA) method to evaluate postural risks, and the Revised NIOSH Lifting Equation with a multitask analysis approach to determine cumulative lifting risks through the Composite Lifting Index (CLI). The findings revealed that incoming goods handling presented the highest ergonomic risk, with an NBM score of 51, a REBA score of 9 (high risk), and a CLI value of 1.065, exceeding the recommended safety threshold. Chemical mixing also demonstrated considerable postural risk with a maximum REBA score of 7, while fuel inspection showed a moderate ergonomic risk with a REBA score of 6, primarily caused by prolonged trunk flexion during manual measurement. The consistency between subjective complaints and objective assessment results confirmed the effectiveness of the integrated evaluation approach in identifying priority areas for intervention. Based on the hierarchy of risk controls, engineering interventions—including the implementation of a scissor lift pallet truck, redesign of the chemical mixing workstation with an ergonomic platform, and replacement of conventional fuel measuring tools with longer or digital measuring devices—were proposed to minimize musculoskeletal risks. The integration of NBM, REBA, and NIOSH multitask analysis provides a comprehensive ergonomic assessment framework that supports safer work systems, improves operational performance, and contributes to sustainable logistics operations by enhancing worker health, productivity, and occupational safety